Share
Notifications

View all notifications

The Roots of the Equation X2 − 3x − M (M + 3) = 0, Where M is a Constant, Are - Mathematics

Login
Create free account


      Forgot password?
ConceptQuadratic Equations

Question

The roots of the equation x2 − 3x − m (m + 3) = 0, where m is a constant, are 

  • A. mm + 3 

  • B. − mm + 3 

  • C. m, − (m + 3) 

  • D. m, − (m + 3) 

Solution

The given quadratic equation is x2 − 3x − m (m + 3) = 0. 

`rArr x^2-[(m+3)-m]x-m(m+3)=0`

`rArr x^2-(m+3)x+mx-m(m+3)=0`

`rArr x{x-(m+3)}+m{x-(m+3)}=0`

`rArr(x+m){x-(m+3)}=0`

`rArrx+m=0` Or `x-(m+3)=0`

`rArr x=-m` or `x=m+3`

Thus, the roots of the given quadratic equation are −m and m + 3. 

The correct answer is B. 

  Is there an error in this question or solution?
Solution The Roots of the Equation X2 − 3x − M (M + 3) = 0, Where M is a Constant, Are Concept: Quadratic Equations.
S
View in app×